Calculated sound velocity and elastic moduli changes in LaOFeP and LiFeAs at the superconducting transition - Abd-Shukor R.; Kong W. (2023)
The changes in elastic modulus and sound velocity of LaOFeP and LiFeAs at their transition temperatures were calculated using various thermodynamic data. Step discontinuities of 59 ppm in the bulk modulus, 101 ppm in Young modulus and 15 ppm in longitudinal sound velocity were estimated for LaOFeP at the superconducting transition. For LiFeAs, the calculated step discontinuities were 25 ppm in the bulk modulus, 38 ppm in Young modulus and 7 ppm in longitudinal sound velocity. 2010 Springer Science+Business Media, LLC.